Sound and literature / - Snaith, Anna (Cambridge University Press, 2020)
What does it mean to write in and about sound? How can literature, seemingly a silent, visual medium, be sound-bearing? This volume considers these questions by attending to the energy generated by the sonic in literary studies from the late nineteenth century to the present. Sound, whether understood as noise, music, rhythm, voice or vibration, has long shaped literary cultures and their scholarship. In original chapters written by leading scholars in the field, this book tunes in to the literary text as a site of vocalisation, rhythmics and dissonance, as well as an archive of soundscapes, modes of listening, and sound technologies. Sound and Literature is unique for the breadth and plurality of its approach, and for its interrogation and methodological mapping of the field of literary sound studies.
Title from publisher's bibliographic system (viewed on 01 Jun 2020).
Keywords: Sound in literature.; Aural history.; Sound; Sounds; Civilization; Modern.